Sistem Informasi Akuntansi, Budaya Organisasi terhadap Kinerja Perusahaan dengan Mediasi Efektivitas Pengendalian Internal - Ramadhani, Tsalisa; Umaimah, Umaimah (Journal of Culture Accounting and Auditing, 2024)
Every company makes internal controls so that their company performs well. A company's performance shows how good and bad a company is. The purpose of this study is to find out how the involvement of accounting information systems and organizational culture affects the company's performance gap, with internal control as a mediating factor. The method used is a quantitative method with purposive sampling techniques on all employees at PT Varia Usaha Fabrication in East Java. The data acquisition process was carried out by conducting an online survey using the Likert scale, followed by analysis using the SEM PLS technique. The results of the study show that the accounting information system and organizational culture do not have a direct effect on the company's performance. However, internal control significantly strengthens this relationship. In contrast, organizational culture does not show any direct influence or significant mediation. Meanwhile, the accounting information system and organizational culture have a direct effect on internal control. The implications of this study underscore the importance of accounting information systems for internal control, so that the increase in the value of a company's internal control will increase the company's performance. The limitations of the study, such as the relatively simple model and limited sample size, indicate the need for further research with more complex models and more representative samples.